2020
DOI: 10.4041/kjod.2020.50.6.383
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, side involvement, phenotype and associated anomalies of Korean patients with craniofacial clefts from single university hospitalbased data obtained during 1998–2018

Abstract: Objective: To investigate the distribution, side involvement, phenotype, and associated anomalies of Korean patients with craniofacial clefts (CFC). Methods: The samples consisted of 38 CFC patients, who were treated at Seoul National University Dental Hospital during 1998-2018. The Tessier cleft type, sex, side involvement, phenotype, and associated anomalies were investigated using nonparametric statistical analysis. Results: The three most common types were #7 cleft, followed by #0 cleft and #14 cleft. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
2
3
1
4
Order By: Relevance
“…It is notable that Tessier clefts 1,2,5,8,9,10,11,12,13 and 14 were not seen in the study population. This is similar to the study by Chug et al (2020) who reported that 1, 2,6,8,9,10,11,12 & 13 were rare: Mishra and Purwar (2009) however, discovered that Tessier cleft 3 and 4 were the rarest cleft in their study [while in this study, we found that Tessier clefts 3 and 4 each accounted for 8.9% of craniofacial clefts in our patients]…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is notable that Tessier clefts 1,2,5,8,9,10,11,12,13 and 14 were not seen in the study population. This is similar to the study by Chug et al (2020) who reported that 1, 2,6,8,9,10,11,12 & 13 were rare: Mishra and Purwar (2009) however, discovered that Tessier cleft 3 and 4 were the rarest cleft in their study [while in this study, we found that Tessier clefts 3 and 4 each accounted for 8.9% of craniofacial clefts in our patients]…”
Section: Discussionsupporting
confidence: 92%
“…Chung et al (2020) noted that the commonest Tessier cleft found in their Korean patients was Tessier 7 [ n = 23, 60.5%]. Although this study shows a slightly higher prevalence of lateral cleft [ n = 14, 31.1%], this is comparable to the prevalence found in the study by Bello et al (2019); Chung et al (2020) and Fogh-Anderson (1965). The diverse discrepancies in which cleft is commoner in the different populations studied may be as a result of geographic or ethnic variations.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Tuy nhiên không có sự khác biệt về khả năng mắc dị tật bẩm sinh khe hở sọ mặt hiếm trên hai giới nam và nữ, tất cả đều có p > 0,05. Nghiên cứu này phù hợp với Chung và cộng sự (2019) [6], nhưng có sự khác biệt so với Kalantar -Hormozi và cs (2017) [4] khi chỉ ra kết quả nữ giới bị ảnh hưởng nhiều hơn nam giới. Sự sai biệt này có thể tới do nghiên cứu trên chủng tộc khác nhau, ý thức khám xét về dị tật sọ mặt của phụ huynh cho trẻ nữ lớn hơn của nam giới.…”
Section: * Giới Tínhunclassified
“…Trong nghiên cứu của chúng tôi, dạng khe hở phổ biến nhất là khe hở số T7 (n = 17; 56.7%), khe hở phổ biến thứ 2 là khe hở số T0 (n = 8; 26,7%) nghiên cứu này phù hợp với nghiên cứu của Chung và cs (2019) [6], nhưng lại khác biệt so với nghiên cứu của Kalantar -Hormozi và cộng sự [4]; Rowland Agbara vs cộng sự [5], cả hai nghiên cứu đều có khe hở phổ biến nhất là khe hở số T0. Sự sai biệt này có thể là do chủng tộc nghiên cứu, cỡ mẫu, cũng như phổ bệnh nhân tới khám tại đơn vị y khoa.…”
Section: * Tỷ Lệ Phân Bố Của Khe Hở Sọ Mặt Hiếm Theo Phân Loại Tessierunclassified